Analysis of proton irradiation products in simulated intersteller dusts by mass spectrometry - KASAMATSU, Takashi; TSUCHIYA, Masahiko; KOBAYASHI, Kensei; KANEKO, Takeo (BUNSEKI KAGAKU, 1996)
It is known that various kinds of organic compounds exist in space. In order to study the possibility of the formation of organic compounds in comets or their precursory bodies (intersteller dust grains), ice mixtures of carbon monoxide (or methane), ammonia and water made in a cryostat at 10 K ("simulated cometary ices") were irradiated with high energy protons. Irradiated ice products were warmed up to room temperature, while sublimed gases were analyzed with a quadrupole mass spectrometer. Some hydrocarbons and alcohols were detected. "Amino acid precursors" (compounds yielding amino acids after hydrolysis) were detected in non-volatile products remaining on the substrate at room temperature. These results suggest the possible formation of organic compounds in interstellar dust grains by cosmic radiation.